Al-Maqrizi and Al-Asadi's Khaldunian Reading of Society, Economy, and Crisis in the Era of the Mamluk State - AlTwahya, Fawzi Khalid Ali; Shilbayeh, Mohammad Mahmoud Bader (Jordan Journal of Social Sciences, 2023)
The aim of this research is to study the impact of Ibn Khaldun's vision of history and urbanization on the expansion of the historical perspective during the Mamluk Era to include the study of Egyptian society in the Mamluk times, and the impact of the economic policy of the Mamluks. To this end, the researchers analyze and present the economic and social ideas and opinions of historians from the Mamluk period, influenced by Ibn Khaldun in his vision of history and urbanism, which were researched through positivist scientific methods, based on extrapolation and analysis in explaining the causes of economic crises in the Mamluk state. The study of Ahmed bin Ali al-Maqrizi and Muhammad bin Khalil al-Asadi comes in the context of economic and social development approaches in the Arab-Islamic heritage.